Unreliable Estimation of Aortic Pulse Wave Velocity Provided by the Mobil‐O‐Graph Algorithm‐Based System in Marfan Syndrome. Issue 9 (7th May 2019) - Salvi, Paolo; Furlanis, Giulia; Grillo, Andrea; Pini, Alessandro; Salvi, Lucia; Marelli, Susan; Rovina, Matteo; Moretti, Francesco; Gaetano, Raffaella; Pintassilgo, Inês; Faini, Andrea; Fabris, Bruno; et al.
Abstract : Background: Several devices have been proposed to assess arterial stiffness in clinical daily use over the past few years, by estimating aortic pulse wave velocity (PWV) from a single measurement of brachial oscillometric blood pressure, using patented algorithms. It is uncertain if these systems are able to provide additional elements, beyond the contribution carried by age and blood pressure levels, in the definition of early vascular damage expressed by the stiffening of the arterial wall. Methods and Results: The aim of our study was to compare the estimated algorithm‐based PWV values, provided by the Mobil‐O‐Graph system, with the standard noninvasive assessment of aortic PWV in patients with Marfan syndrome (ie, in subjects characterized by premature aortic stiffening and low blood pressure values). Aortic stiffness was simultaneously evaluated by carotid‐femoral PWV with a validated arterial tonometer and estimated with an arm cuff–based ambulatory blood pressure monitoring Mobil‐O‐Graph device on 103 patients with Marfan syndrome (50 men; mean±SD age, 38±15 years). Aortic PWV, estimated by the Mobil‐O‐Graph, was significantly ( P <0.0001) lower (mean±SD, 6.1±1.3 m/s) than carotid‐femoral PWV provided by arterial tonometry (mean±SD, 8.8±3.1 m/s). The average of differences between PWV values provided by the 2 methods (±1.96×SD) was −2.7±5.7 m/s. Conclusions: The Mobil‐O‐Graph provides PWV values related to an ideal subject for a given age and blood pressure, but it is not able to evaluate early vascular aging expressed by high PWV in the individual patient. This is well shown in patients with Marfan syndrome.